AN ANALYSIS OF THE FACTORS AFFECTING THE IMPLEMENTATION OF CAMBODIAN FINANCIAL REPORTING STANDARD FOR NOT-FOR-PROFIT ENTITIES - Lim, Siphat; Flores, Edman Padilla (International Journal of Accounting & Finance Review, 2023)
The adoption of the Cambodia Financial Reporting Standard (CFRS) for Not-For-Profit Entities (NFPEs) is crucial for both the entities themselves and the Accounting and Auditing Regulator (ACAR). Despite the large number of registered not-for-profit entities in Cambodia, not all of them have embraced the use of CFRS. This study aims to analyze the factors that influence the likelihood of adopting CFRS for NFPEs through a logit regression model. Six factors are identified, including three observed variables (entity size, fear of penalties, and ease of accessing funds) and three latent variables (valuation of accounting items, entities’ readiness, and consistency with tax regulations). Data was collected from 109 entities. The empirical findings reveal that five out of the six factors are statistically significant in explaining the likelihood of entities adopting CFRS for NFPEs. However, the entities’ readiness to adopt CFRS was found to be statistically insignificant. The estimated parameter values for the significant factors align with expectations. The Pseudo-R2 suggests that approximately 61.8 percent of the variation in the dependent variable can be attributed to the independent variables. It is important for not-for-profit entities and the ACAR to consider these significant factors when promoting the adoption of CFRS for NFPEs. Future research could further investigate the reasons behind the lack of significance in the entities’ readiness factor and explore additional factors that may influence the likelihood of CFRS adoption. JEL Classification Codes: M10, M40, M41, M48.